Effect of estrogen on growth and development of nerve cell in cerebellum of rat - CHEN Zheng-li; LUO Qi-hui; FAN Guang-li (浙江大学学报. 农业与生命科学版)
In order to study the effect of estrogen on the development and neurocrine of nerve cell culture vitro of cerebellum, select the nerve cell of cerebellum of one day rat, then observe the growth and development of nerve cell after treatment with 17β-estradiol, also detect the expression of estrogen receptor (ER), nerve growth factor (NGF) and choline acetyl transferase (ChAT) using the technique of immunohistochemistry SP. The results show that estrogen play an important role in the growth and development of nerve cell, which enhance the growth of cell body, elongation of neurite. In addition, estrogen can prolong the survival time of nerve cell, prevent the degeneration, depauperation and death. The effect of estrogen on neurocrine of nerve cell culture in vitro is significant, which can enhance the expression of ER, NGF and ChAT, increase the number of positive neurons, and the expression of those positive production depend on the culture time. It is suggested that estrogen may play an important role directly or indirectly in nerve cell culture in vitro by ER, which has the function of neurotrophy and regulation of neurotransmission in cerebellum of rat.